VIRTUAL REALITY: U.S. INFORMATION SECURITY THREATS CONCEPT AND ITS INTERNATIONAL DIMENSION - E. V. Batueva (MGIMO University Press, 2014)
The development of ICT and the formation of the global information space changed the agenda of national and international security. Such key characteristics of cyberspace as openness, accessibility, anonymity, and identification complexity determined the rise of actors in cyber space and increased the level of cyber threats. Based on the analyses of the U.S. agencies' approach, the author defines three major groups of threats: use of ICT by states, criminals and terrorists. This concept is shared by the majority of the countries involved in the international dialogue on information security issues and is fundamental for providing cyber security policy on both national and international levels. The United States is developing a complex strategy for cyber space that includes maximization of ICT's advantages in all strategically important fields as well as improvement of national information systems and networks security. On the international level the main task for the American diplomacy is to guarantee the U.S. information dominance. The United States is the only country that takes part practically in all international and regional fora dealing with cyber security issues. However process of the development of a global cyber security regime is not going to be fast due to countries' different approaches to key definitions and lack of joint understanding of cyber security issues as well as due to the position of the countries, among all the United States, that are not interested in any new obligatory international norms and principles. Such American policy aims at saving the possibility of using cyberspace capacity in reaching political and military goals, thus keeping the global leadership.